A gift of prophecy : Essays in celebration of the life of Robert Eugene Marshak - Sudarshan, E C George (Singapore World Scientific, 1994)
Robert Eugene Marshak (1916-92) devoted much of his life to helping other people carry out scientific research and gather to discuss their work. In addition to his scientific statesmanship, he was an extraordinarily gifted research scientist, and many of his scientific contributions have been prophetic. This book pays homage to his creativity and continuing work, with contributions from many of the people whose lives have been influenced by him.
Keywords: Cơ bản